Ms. PHOTO SOTRY 3, INTEGRATING TECHNOLOGY IN WRITING CLASS FOR EFL STUDENTS - Khomarudin Kamsina (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2020)
AbstrackThe objective of the study is to investigate the students’ perceptions of using a Ms. Photo Story 3 for writing practice among EFL learners in an English for senior high school class. The method of research design was employed descriptive qualitative techniques. Thirty eight senior high school students in writing class were introduced to the Ms. Photo Story 3 for writing practice. After using the application in class, students completed a survey questionnaire and ten students were selected for follow-up interviews based on their writing proficiency. Survey results showed that the majority of students held favorable attitudes towards using Ms. Photo Story 3 as a writing tool. The evidence obtained from a multiple choice question in the survey showed that a majority of the students benefited by using the Ms. Photo Story 3 to increase their writing. Moreover, interview data revealed that the Ms. Photo Story 3 had a positive effect on writing skill development. Finally, eight of the ten interview participants suggested that Ms. Photo Story 3 could be utilized in future writing classes. Further discussions of the benefits of adopting Ms. Photo Story 3 writing software such as increased learner motivation and learner autonomy also indicate that this kind of software can be a useful support tool in the EFL classroom. Keywords: Ms. Photo story, writing skill, and EFL learners.